Public Oversight and Performance Measurement in the Public Sector Entities - Sunčica Milutinović; Ivana Medved; Dragomir Dimitrijević (Anali Ekonomskog fakulteta u Subotici, 2024)
The existence of the public sector is conditioned by meeting the needs of citizens for public goods and services. Business under constant public scrutiny poses challenges to public sector entities in the form of effectiveness and efficiency in providing services, on the one hand, and achieving satisfactory financial performance, on the other. Measuring the performance of entities in the public sector can be problematic precisely for the reason that it is necessary to measure the performance of entities whose operations are aimed at meeting public needs and not at making a profit. Therefore, the goals of these entities are taken as a starting point when establishing an adequate performance measurement system. Bearing in mind that the public sector is at the service of the citizens of a country, the question of measuring business performance, as well as the question of public supervision in public sector entities, arises. State audit, financial management and control and internal audit, as elements of public supervision, should ensure fair and true presentation of results and performance of business in public sector entities.